2019
DOI: 10.1093/eurheartj/ehz429
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of peri-procedural transcatheter heart valve embolization and migration: the TRAVEL registry (TranscatheteR HeArt Valve EmboLization and Migration)

Abstract: Aims Peri-procedural transcatheter valve embolization and migration (TVEM) is a rare but potentially devastating complication of transcatheter aortic valve implantation (TAVI). We sought to assess the incidence, causes, and outcome of TVEM in a large multicentre cohort. Methods and results We recorded cases of peri-procedural TVEM in patients undergoing TAVI between January 2010 and December 2017 from 26 international sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 16 publications
1
99
1
Order By: Relevance
“…According to the consensus, the definition of BVF is adverse events are the use of self -expanding or first -generation prostheses and the presence of a bicuspid aortic valve. 22 More frequent and more severe PVR has been reported after TAVI than after surgical aortic valve replacement (SAVR) with a rate of incidence ranging from 1% to 3% for moderate PVR to 29% to 36% for mild PVR. 23 In the PARTNER (Placement of Aortic Transcatheter Valve) trial, 24 at 1-year follow -up, the worsening of PVR was found to be associated with a significant increase in mortality and hospitalizations.…”
mentioning
confidence: 99%
“…According to the consensus, the definition of BVF is adverse events are the use of self -expanding or first -generation prostheses and the presence of a bicuspid aortic valve. 22 More frequent and more severe PVR has been reported after TAVI than after surgical aortic valve replacement (SAVR) with a rate of incidence ranging from 1% to 3% for moderate PVR to 29% to 36% for mild PVR. 23 In the PARTNER (Placement of Aortic Transcatheter Valve) trial, 24 at 1-year follow -up, the worsening of PVR was found to be associated with a significant increase in mortality and hospitalizations.…”
mentioning
confidence: 99%
“…Despite these precautions, two patients with TAVR‐H developed late PVL and ultimately, proximal device migration. Device migration should be a clinical rarity 21 that occurs primarily perioperatively with an incidence of approximately 1% 22 . The use of self‐expanding, first‐generation, and resheathable devices, higher cover index, sizing error, larger aortic root dimensions, and the presence of bicuspid aortic valve all predispose to device migration, but were not the cause of migration in our two patients.…”
Section: Discussionmentioning
confidence: 77%
“…Considered a relatively safe procedure, valve embolization during TAVR is a fairly uncommon phenomenon. According to the TranscatheteR HeArt Valve EmboLization and Migration (TRAVEL) registry, valve embolization occurred in 273 of 29,636 patients (0.92%), 2 similar to other registries placing this risk at about 1% 3,4 . It is possible, however, that the prevalence of embolization is actually higher due to possible under‐reporting.…”
Section: Introductionmentioning
confidence: 79%